2018
DOI: 10.4103/1673-5374.224383
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency pulsed electromagnetic field pretreated bone marrow-derived mesenchymal stem cells promote the regeneration of crush-injured rat mental nerve

Abstract: Bone marrow-derived mesenchymal stem cells (BMSCs) have been shown to promote the regeneration of injured peripheral nerves. Pulsed electromagnetic field (PEMF) reportedly promotes the proliferation and neuronal differentiation of BMSCs. Low-frequency PEMF can induce the neuronal differentiation of BMSCs in the absence of nerve growth factors. This study was designed to investigate the effects of low-frequency PEMF pretreatment on the proliferation and function of BMSCs and the effects of low-frequency PEMF pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…BM-MSCs were isolated following a previously described method 27 . Briefly, rats were sacrificed and their hind limbs were harvested, bone marrow was flushed out and collected in Dulbecco's Modified Eagle's Medium (DMEM) (Gibco, Grand Island, NY, USA) supplied with 10% fetal bovine serum (Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…BM-MSCs were isolated following a previously described method 27 . Briefly, rats were sacrificed and their hind limbs were harvested, bone marrow was flushed out and collected in Dulbecco's Modified Eagle's Medium (DMEM) (Gibco, Grand Island, NY, USA) supplied with 10% fetal bovine serum (Gibco).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the authors also noted improved locomotor function and upregulation in BDNF and NGF in the treatment group. Comparably, Seo et al have used BM-MSCs pretreated with low-frequency, pulsating electromagnetic fields (LF-PEMFs) to remedy a crush-injured rat mental nerve (Seo et al, 2018). The results demonstrated that injection of pre-treated BM-MSCs led to a higher count of myelinated axons, with higher overall axon density.…”
Section: Electromagnetic Fieldsmentioning
confidence: 99%
“…Oral and maxillofacial surgeries that are performed especially in the lower jaw including impacted third molar surgery, dental implant applications, cyst or tumor operations, orthognathic surgery, pre-prosthetic surgery, arthroscopic surgery, salivary gland surgery, operations in maxillofacial trauma, and injection injuries can damage the inferior alveolar nerve, mental nerve or lingual nerve by crushing or compressing it (Cornwall and Radomisli 2000;Er et al 2016;KÜÇÜKKURT et al 2018). The total percentage of the inferior alveolar nerve and lingual nerve injuries varies between 0.5% and 5% after the extraction of the lower third molar (Swanson 1991 As a result of these damages, complaints such as permanent anesthesia, dysesthesia, pain, paresthesia (burning, stinging, numbness or tingling sensation) related to the affected region can be observed (Seo et al 2018;KÜÇÜKKURT et al 2018). Generally, spontaneous recovery is observed in most of the patients within 6-8 weeks, but the sensory loss may persist for 6 months or longer, and permanent neuropathic disorders may occur in such cases (Smith and Lung; Pogrel and Kaban 1993; KÜÇÜKKURT et al 2018).…”
Section: Introductionmentioning
confidence: 99%